Sistematični pregled literature s področja ambivalentnega seksizma - Svetek, Mojca (Psihološka obzorja (Ljubljana), 2017)
Manifestations of sexism are under the constant inf luence of social changes and changes in gender relations. This paper presents modern forms of sexism, with an emphasis on the ambivalent sexism theory (Glick and Fiske, 1996). Ambivalent sexism theory addresses sexism not only on societal but also on interpersonal and personal level. In addition, this article provides a comprehensive review of the empirical findings in the field of benevolent and hostile sexism and their effect on close relations, sexual violence, beauty ideals and practices, women's self-esteem, and their career decisions and aspirations. Finally, I place ambivalent sexism theory into the broader societal and psychological context and discuss the possibilities of surmounting current sexist ideologies and practices.
Keywords: medosebni odnosi; razlike med spoloma; opolnomočenje; odnosi med spoloma; seksizem; socialne norme; samopodoba; spolno nasilje; kariera; Kariera people